Sistemas de numeração posicionais e não posicionais - Santos, Anderson Flávio dos [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The necessity of using numbers is a historical process and essencial to the organization of human life, although it is an abstract concept. Since Early Middle Ages, when human beings still lived in caves, the need for counting had always existed because fishes, herds, plantations had to be counted. Even nowadays the most diverse and developed technologies use numbers like the computacional binary numeral system. The aim of this paper is to explain how numeral systems have been used throughout history, their necessity, calculation and aplication. Besides this, comparisons between the most used systems will be presented, distinguishing positional and non positional numeral systems. It is also intended to suggest reflection about this systems models advantages and disadvantages. Also pratical activities applied to children in fourth and fifth grades of primary and secondary school results will be present. The purpose is showing how children understand numbers positioning of decimal number system in order to highlight that the memorizing habit prevails performing basic operations of this system due to the fact people do not understand it. This fact makes the students of Brazilian schools do not have basic math skills, and, consequently, the country does not present desirable results on international assessments. In summary, the main purpose of this paper is being an opportunity for reflection presenting math history, demonstrating numbering systems simple concepts and showing that someone really learns to manipulates numbers when they are really understood

A necessidade do uso dos números é um processo histórico e indispensável à organização da vida humana, apesar de ser um conceito abstrato. Desde a idade antiga, quando os humanos ainda moravam em cavernas, a necessidade da contagem sempre esteve presente, pois contavam peixes, rebanhos, plantações. Até mesmo nos dias de hoje, as mais variadas e desenvolvidas práticas tecnológicas utilizam-se dos números, citando, como exemplo, o sistema binário computacional. O objetivo deste trabalho é explicar como os sistemas de numerações são utilizados ao longo da história, suas necessidades, cálculos e aplicações. Além disso, serão apresentadas comparações entre os sistemas mais utilizados, fazendo distinção entre sistemas numéricos posicionais e não posicionais. Pretende-se, também, propor uma reflexão sobre as vantagens e desvantagens desses modelos de sistemas. Ainda serão apresentados resultados de atividades práticas aplicadas com crianças que estão cursando o 4º e 5º ano do Ensino Fundamental. Objetiva-se mostrar como as crianças compreendem o posicionamento dos números dentro do sistema numérico decimal, de modo a evidenciar que o hábito da memorização é predominante para a realização das operações básicas desse sistema em decorrência do seu não entendimento. Tal fato faz com que os alunos das escolas brasileiras não tenham conhecimentos matemáticos básicos, e, consequentemente, com que o país não apresente resultados desejáveis nas avaliações internacionais. Em síntese, pretende-se que este trabalho seja uma oportunidade de reflexão ao passar pela história da matemática, por demonstrações de conceitos simples desses sistemas de numeração e explicitar que uma pessoa aprende realmente a manipular os números quando faz real entendimento destes
Keywords: Matemática - Estudo e ensino; Sistema decimal; Numeração; Contagem; Matemática - Metodologia; Mathematics Study and teaching